Inhibitory Mechanism of Monensin on High K+-Induced Contraction in Guniea-Pig Urinary Bladder - Takeharu Kaneda; Mayumi Takeuchi; Kazumasa Shimizu; Norimoto Urakawa; Shinjiro Nakajyo; Mariko Mochizuki-Kobayashi; Fukiko Ueda; Ryo Hondo (Elsevier, 2006)
Abstract.: In this study, we examined the inhibitory mechanism of monensin on high K+-induced contraction in guinea-pig urinary bladder. The relaxant effect of monensin (0.001 - 10 µM) was more potent than those of NaCN (100 µM - 1 mM) and forskolin (3 - 10 µM). Monensin (0.1 µM), NaCN (300 µM), or forskolin (10 µM) inhibited high K+-induced contraction without decreasing [Ca2+]i level. Monensin and NaCN remarkably decreased creatine phosphate and ATP contents. Monensin and NaCN inhibited high K+-induced increases in flavoprotein fluorescence, which is involved in mitochondrial respiration. Forskolin increased cAMP content but monensin did not. Monensin increased Na+ content at 10 µM but not at 0.1 µM that induced maximum relaxation. In the α-toxin-permeabilized muscle, forskolin significantly inhibited the Ca2+-induced contraction, but monensin did not affect it. These results suggest that the relaxation mechanism of monensin in smooth muscle of urinary bladder may be an inhibition of oxidative metabolism. Keywords:: monensin, urinary bladder, phosphocreatine, Na+ content